Employee Development by Talent Management - Fajčíková, Adéla; Fejfarová, Martina; Urbancová, Hana (Univerzita Pardubice, 2016)
Employee development is an important part of the modern concept of human resource management based on the development of potential and competencies of employees to achieve a competitive advantage. Therefore, talent management is becoming a crucial part of the personnel strategy of organisations not only in the Czech Republic but also globally. The aim of this article is to evaluate the approach of organisations in the Czech Republic towards employee training and development and the extent of talent management implementation. A partial aim is to examine relationships between the selected qualitative variables. Results were obtained through a questionnaire survey (n = 389) among organisations conducting business in the Czech Republic. Results of the research showed that 54.8% of the organisations do not implement talent management. Only 11.5% of the organisations have a talent management strategy. An alarming fact is in particular one that most of the organisations not implementing talent management do not find it important (46.5%). Significant factors influencing the implementation of activities related to talent management in an organisation include the size of the organisation and the market in which the organisation operates. The significance of the sector and the area of operation has not been proved.
Keywords: Development; Employee; Human resource management; Organisation; Survey; Talent management; Training; O15; D83; M12